Medio Oriente. Una ventana de oportunidad para México - Fajer Flores, Ana Luisa (Revista Mexicana de Política Exterior, 2022)
The Middle East indubitably represents a window of opportunity for Mexico in its efforts to bolster the economic component of its foreign policy as an effective means of promoting the country’s development. In her essay, Ana Luisa Fajer refers to accepted definitions of the term Middle East for purposes of Mexico’s foreign policy before going on to discuss the factors that make this a strategically important region for Mexico, whose diplomatic relations with the major countries in this geographical area reflect bilateral ties of varying degrees in political, economic, commercial and cultural spheres. According to the author, the Middle East offers enormous opportunities for Mexican companies with the potential to invest there, plus the chance to foster exports and attract investment, particularly from Persian Gulf countries, in addition to promoting Mexico’s tourism and cultural attractions. However, achieving this will depend on whether or not agreements can be reached at multilateral forums on issues relevant to Mexico and the extent to which we are able to avail ourselves of our existing network of diplomatic representation to promote Mexican exports and attract foreign investment, among other measures. Ana Luisa Fajer concludes by underlining some of the challenges the Middle East poses for Mexico in this respect, placing emphasis on the strategies that have been drawn up to address these.